18. Comprehensive geriatric assessment in older post-stroke patients: A cross-sectional study - Huong, Nguyen Thi Thu; Anh, Nguyen Trung; Luc, Tran Viet (Tạp chí Nghiên cứu Y học, 2023)
This study aims to identify the components of comprehensive geriatric assessment (CGA) in older post-stroke patients. A cross-sectional study was conducted on 137 post-stroke patients aged ≥ 60 years old being treated at the National Geriatric Hospital. The components of CGA were assessed as medical status (nutrition; urinary incontinence, frailty, visual and hearing ability); functional status (Barthel index, instrumental activity daily living, risk of fall); neuropsychological status (cognition and depression). 66.4% of patients had an ischemic stroke, and 33.6% of patients had a hemorrhage stroke. In both ischemic and hemorrhagic post-stroke groups, domains such as functional impairment, malnutrition, vision loss, high risk of falls, cognitive impairment, and depression account for a high rate (≥ 50%). There was no statistically significant difference in rates of CGA domains between the two groups of patients with ischemic and hemorrhage stroke. This study showed a high prevalence of most components of CGA in older post-stroke patients both in ischemic stroke and hemorrhage stroke patients.